AB0749 Don't forget the caregivers of patients with systemic sclerosis. (12th June 2018) - Boonstra, M.; Stoop, D.F.; Huizinga, T.W.; Vliet Vlieland, T.P.; de Vries-Bouwstra, J.K.
Abstract : Background: Systemic sclerosis (SSc) is a disease with considerable physical and psychosocial impact. Previous studies among partners of patients with other chronic diseases, such as Parkinson's and stroke, showed that 6%–25% of caregivers experience high levels of stress related to caregiving. To our knowledge, the burden experienced by caregivers of patients with SSc has not been determined so far. Objectives: To evaluate perceived strain, quality of life and health care needs among SSc caregivers. Methods: During a patient information meeting, companions of SSc patients were invited to complete 3 questionnaires: 1. The Caregiver Strain Index questionnaire (CSI), in which a score ≥7 indicates high care burden, 2. Short Form-36 (SF-36): a measure of self-reported Quality of Life (QoL) and 3. a self-designed questionnaire on the needs and preferences for caregiving support. Caregivers with and without high care burden were compared regarding their general characteristics and Qol. Results: Thirty-six SSc caregiver filled out questionnaires (n=31 completed the CSI questionnaire). Respondents were mostly men (64%), on average 62 years old (SD 14), 35% (n=11) had a paid job, and 50% (n=18) suffered from chronic disease. The majority was in a spousal relationship (75%) with the SSc patient and 56% of patients had been diagnosed with SSc more than 5 years ago. Nineteen percent of patients (n=7) needed daily personal caregiving and 25% (n=9) was transport-dependent. Median CSI was 2 (range 0 to 5), and 6/31 (19%) perceived high care burden(CSI ≥7). Caregivers with high care burden were significantly more often involved in daily personal caregiving of the patients (3/6 vs. 2/25). Although not statistically significant, all caregivers perceiving a high burden were spouses, while the remaining caregivers had varying relationships with SSc patients. SF-36 summary scale scores were similar in both groups (table 1). Regarding needs and preferences of caregivers, 15% (n=5) reported a need for additional individual information, and 21% (n=7) a need for contact with fellow caregivers of patients, preferably during information meetings. 1 Fisher's exact 2 Mann-Withney U *n=35, **n=31, ***n=28, ****n=19 Conclusions: Within a small group of SSc caregivers, 19% experienced high care burden. In particular caregivers involved in personal caregiving seem to be at risk for increased strain related to caregiving. The results of the current study can direct clinical practice aiming at support of the caregivers. Disclosure of Interest: None declared